Identification of Mud volcano’s structure using gravity satellite and fault fracture density analysis: case study Ciuyah Mud Volcano, Kuningan, West Java - Agustine, Eleonora; Pranatikta, Krishna Agra; Budianto, Muhammad Abdillah; Mariyanto,; Iriyanti, Mimin; Hapsoro, Cahyo Aji; Indriana, Rina Dwi (Penerbit Universiti Kebangsaan Malaysia, 2023)
Mud volcanoes, known as mud extrusion phenomenon, is a geological feature that expels suspended fine-grained sedimentary materials and fluids to the surface due to buoyancy and pressure difference. This geological feature is found almost all over the world and formed in compressional tectonic environments, one of which is the Ciuyah Mud Volcano, Kuningan, Indonesia. Previous studies have shown that the appearance of the mud volcano was influenced by tectonic activity that formed a ‘hypothetical’ fault structure as a pathway for mud migration and extrusion to the surface. Integration of geophysical studies using satellite gravity and geology using fault fracture density analysis was conducted to prove the existence of the ‘hypothetical’ fault structure. The results show that the mud volcano site is located in a low to high gravity anomaly pattern associated with significant density contrast differentiation followed by the maximum value of FHD and low-high SVD pattern oriented west southwest - east northeast (WSW - ENE). The gravity anomaly pattern can be associated with the presence of faults. This is reinforced by the fault fracture density map which shows that the mud volcano site is located in a medium to high fracture density zone (weak zone) associated with good permeability conditions below the surface. Thus, the research results have proven the existence of a ‘hypothetical’ fault as the migration and extrusion pathway of Ciuyah Mud Volcano mud that has been studied previously.